Carbon Trading In Sharia Perspective: Fiqh Analysis And Its Implementation In Indonesia - Adnan, Mohammad; Uyuni, Badrah (Jurnal Pengembangan Masyarakat Islam, 2025)
Carbon trading is an economic instrument that controls greenhouse gas (GHG) emissions and promotes sustainable development. This study examines the concept of carbon trading from an Islamic perspective, analyzing its compliance with fiqh muamalah principles and its regulatory framework in Indonesia. Using a qualitative research method with a descriptive-analytical approach, the findings indicate that carbon trading can be classified as Ba’i al-Huquq al-Ma’nawiyyah (the sale of intangible rights), which has a legitimate basis in Islamic jurisprudence. However, potential risks such as gharar (uncertainty), riba (usury), and speculation require further scrutiny to ensure full compliance with maqashid shariah (the objectives of Islamic law). The study highlights the need for regulatory adjustments to align carbon trading mechanisms with Islamic economic principles, ensuring they function as Shariah-compliant financial instruments. This research contributes to the discourse on Islamic finance and green economy, offering policy recommendations for regulators and stakeholders involved in carbon markets.